ACCELERATED HUMORAL (ANTIBODY-MEDIATED) REJECTION OF THE CARDIAC ALLOGRAFT (A CASE REPORT) - A. G. Kupriyanova; L. V. Beletskaya; V. A. Zaidenov; I. M. Iljinsky; N. P. Mogeiko; Z. V. Tatievskaya; D. V. Shumakov (Вестник трансплантологии и искусственных органов)
In the article there is described the case of the accelerated humoral (antibody-mediated) rejection of the cardiac allograft with morphologic and immunohistochemical details revealed at the investigation of the endomyocardial biopsy and myocardial autopsy.